2011
DOI: 10.1002/ptr.3597
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Herbal Extract (EstroG‐100) on Pre‐, Peri‐ and Post‐Menopausal Women: A Randomized Double‐blind, Placebo‐controlled Study

Abstract: This clinical research study was designed to evaluate the efficacy of a new herbal product, EstroG-100, containing a mixture of standardized extracts of Cynanchum wilfordii, Phlomis umbrosa and Angelica gigas, on menopausal symptoms. This randomized double-blind, placebo-controlled trial was performed for 12 weeks with 64 pre-, peri- and postmenopausal White Hispanic, White non-Hispanic and African American women who were randomly allocated to either the EstroG-100 group (n = 31) or the placebo group (n =  33)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 15 publications
2
37
0
Order By: Relevance
“…Its dried root extract is marketed as a dietary supplement for pain relief and memory enhancement in the United States and globally. AGN-containing multiple herbal supplements have been tested and found efficacious for relieving postmenopausal symptoms in US women (3). …”
Section: Introductionmentioning
confidence: 99%
“…Its dried root extract is marketed as a dietary supplement for pain relief and memory enhancement in the United States and globally. AGN-containing multiple herbal supplements have been tested and found efficacious for relieving postmenopausal symptoms in US women (3). …”
Section: Introductionmentioning
confidence: 99%
“…2) In April 2015, an investigation into CWR-containing products by the Korea Food and Drug Administration revealed that Cynanchum auriculatum ROYLE ex WIGHT (Asclepiadaceae) was illegally used for 65% of these products. 3,4) The roots of C. auriculatum have been traditionally used as Cynanchi Auriculati Radix CAR, in China, but CAR is now listed as a toxic plant by the U.S. Food and Drug Administration (FDA) because of its ability to initiate miscarriage in female pigs.…”
mentioning
confidence: 99%
“…In the treatment of menopausal symptoms, herbal mixtures containing C. wilfordii have been used to improve symptoms including hot flashes, vaginal dryness, night sweats, and insomnia [18]. However, the anti-osteoporotic effect of C. wilfordii in an ovariectomized (OVX)-induced rat model and on osteoclastic bone resorption has not been reported.…”
Section: -470mentioning
confidence: 99%